Cytogenotoxic screening of the natural compound niga-ichigoside F1 from Rubus imperialis (Rosaceae) - Almeida-Terassi, Laíza Moura; Castanha, Ana Paula Martins; Alves, Greice Rafaele; Cechinel-Filho, Valdir; Niero, Rivaldo; O'Neill de Mascarenhas Gaivão, Isabel; de Oliveira, Liana Martins; de Lima, Luan Vitor Alves; Mantovani, Mário Sérgio; Maistro, Edson Luis [UNESP] (My University, 2024)
Rubus imperialis Chum. Schl. (Rosaceae) have demonstrated some pharmacological activities, including gastroprotective action. However, genotoxic effects of R. imperialis extract was also reported. Since niga-ichigoside F1 (NIF1) is a major compound of this plant species, and which has proven pharmacological properties, it is essential to investigate whether this compound is responsible for the observed toxicity. Therefore, the objective of this study was to analyze the effects of NIF1 on HepG2/C3A cells for possible cytogenotoxicity, cell cycle and apoptosis influence, and expression of genes linked to the DNA damage, cell cycle, cell death, and xenobiotic metabolism. The results showed no cytogenotoxic effects of NIF1 at concentrations between 0.1 and 20 μg/ml. Flow cytometry also showed no cell cycle or apoptosis disturbance. In the gene expression analysis, none of the seven genes investigated showed altered expression. The data indicate that NIF1 has no cytogenotoxic effects, and no interruption of the cell cycle, or induction of apoptosis, apparently not being responsible for the cytotoxic effects observed in the crude extract of R. imperialis.
Keywords: apoptosis analysis; cell cycle analysis; comet assay; gene expression; micronucleus test; Niga-ichigoside F1 toxicity